1997
DOI: 10.1007/s004380050495
|View full text |Cite
|
Sign up to set email alerts
|

The IBP genes of maize are expressed in non-meristematic, elongating cells of the seedling and in abortive floral organs

Abstract: The transcription start site of the maize Shrunken-1 (Sh-1) gene is sufficient for transcriptional initiation in the absence of other promoter elements and is recognized in vitro by the Initiator Binding Protein (IBP). We describe here in situ hybridization experiments performed on various maize tissues to quantify IBP transcription at the cellular level. IBP transcripts are found in the endosperm and in differentiating, enlarging cells of the shoot and the root of the maize seedling. This expression pattern o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…SuSy is believed to function in channeling UDP-glucose from sucrose to various -glucan synthases for cellulose biosynthesis. Its activity was positively correlated with cell wall biosynthesis (Klinge et al 1997) and with cell wall thickening by cellulose deposition in roots in response to stress (Albrecht and Mustroph 2003). In this study, SuSy 1 was identiWed with high expression in Chisholm-T after 3 h and 7 days of Al exposure.…”
Section: Defense Responsive Genesmentioning
confidence: 99%
“…SuSy is believed to function in channeling UDP-glucose from sucrose to various -glucan synthases for cellulose biosynthesis. Its activity was positively correlated with cell wall biosynthesis (Klinge et al 1997) and with cell wall thickening by cellulose deposition in roots in response to stress (Albrecht and Mustroph 2003). In this study, SuSy 1 was identiWed with high expression in Chisholm-T after 3 h and 7 days of Al exposure.…”
Section: Defense Responsive Genesmentioning
confidence: 99%
“…In Arabidopsis, several R1-MYB proteins, such as EPR1 (Kuno et al , 2003), LHY (Schaffer et al , 1998), and CCA1 (Wang and Tobin, 1998), have been isolated and confirmed as circadian oscillators involved in developmental modulation in plants. In maize, R1-MYB affects developing cells in the root or shoot apex, as well as the gibberellin hormone balance (Klinge et al , 1997). The R1-MYB protein was also reported to participate in the stress response process (Cheng et al , 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This subfamily is further divided into several subgroups, including CCA1-like, I-box-binding-like, TBP-like, TRF-like, CPC-like and other MYB-related proteins (Yanhui et al, 2006). They act as circadian oscillators in developmental modulation (Wang and Tobin, 1998;Kuno et al, 2003, Schaffer et al, 1998, regulate hormone balance (Klinge et al, 1997) and are involved in stress responses (Cheng et al, 2013). 1R MYB TFs are also reported as potential regulators of phenylpropanoid biosynthesis in many plants (Feller et al, 2011;Yi et al, 2010;Zhang et al, 2009;Zhu et al, 2009;Nemie-Feyissa et al, 2014;Dubos et al, 2008;Matsui et al, 2008).…”
Section: Introductionmentioning
confidence: 99%